A Versatile Skin-Derived Extracellular Matrix Hydrogel-Based Platform to Investigate the Function of a Mechanically Isolated Adipose Tissue Stromal Vascular Fraction - Xue Zhang; Jan Aart M. Schipper; Rutger H. Schepers; Johan Jansma; Fred K. L. Spijkervet; Martin C. Harmsen (Biomolecules, 2024)
Introduction: To accelerate cutaneous wound healing and prevent scarring, regenerative approaches such as injecting a mechanically derived tissue stromal vascular fraction (tSVF) are currently under clinical and laboratory investigations. The aim of our study was to investigate a platform to assess the interaction between skin-derived extracellular matrix (ECM) hydrogels and tSVF and their effects on their microenvironment in the first ten days of culture. Material and Methods: A tSVF mixed with ECM hydrogel was cultured for ten days. After 0, 3, 5, and 10 days of culture viability, histology, immunohistochemistry, gene expression, and collagen alignment and organization were assessed. Results: The viability analysis showed that tSVF remained viable during 10 days of culture and seemed to remain within their constitutive ECM. The fiber analysis demonstrated that collagen alignment and organization were not altered. No outgrowth of capillaries was observed in (immuno)histochemical staining. The gene expression analysis revealed that paracrine factors TGFB1 and VEGFA did not change and yet were constitutively expressed. Pro-inflammatory factors IL1B and IL6 were downregulated. Matrix remodeling gene MMP1 was upregulated from day three on, while MMP14 was upregulated at day three and ten. Interestingly, MMP14 was downregulated at day five compared to day three while MMP2 was downregulated after day zero. Conclusions: Skin-derived ECM hydrogels appear to be a versatile platform for investigating the function of a mechanically isolated adipose tissue stromal vascular fraction. In vitro tSVF remained viable for 10 days and sustained the expression of pro-regenerative factors, but is in need of additional triggers to induce vascularization or show signs of remodeling of the surrounding ECM. In the future, ECM-encapsulated tSVF may show promise for clinical administration to improve wound healing.